Exploring Students’ Geometrical Thinking Through Dynamic Transformations Using 3D Computer-Based Representations - Christos Markopoulos; Patrick Bruck; Koralia Petta (Journal of Mathematics Education at Teachers College, 2022)
This paper examines Grade 6 students’ thinking about geometrical solids and their properties in the context of a computer-based task. The main focus is to explore how students interact with a number of tasks based on the dynamic transformation of computer-based representations of 3D solids in a geometry classroom with the aid of a Dynamic Geometric Environment. The analysis of two teaching experiments suggests that the dynamic transformations of geometrical solids encourage the students to investigate relationships between the solids and their properties and their 2D representations. Through the tasks, students realize the existence of non-trivial conventions in 2D representations and become aware that angles and edge dimensions may be distorted. The study provides insight into student learning around geometric solids and their properties, and consequently an opportunity to enhance the teaching of 3D geometry.